DIAGRAM Report: AI 2018 - Coleman-Turner Clayton Lewis (DIAGRAM Center, 2018)
Artificial Intelligence in Inclusive Education Clayton Lewis Coleman-Turner Professor of Computer Science University of Colorado Boulder What is Artificial Intelligence The term artificial intelligence (AI) was defined in 1956 and refers to computer systems that are able to perform tasks that normally require human intelligence or mimic cognitive functions typically associated with natural intelligence displayed by humans. The field was […]